Pelaksanaan Pengawasan Keamanan Pangan dalam Rangka Penerbitan Izin Edar Pirt (Produk Industri Rumah Tangga) di Dinas Kesehatan Kabupaten Bengkulu Utara - Wulan Angraini; Via Dariska Ulandari; Eva Oktavidiati; Hasan Husin; Riska Yanuarti (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Distribution licenses for Household Industry Products (PIRT) are issued by the North Bengkulu Regency Health Office, which carries out food safety monitoring. In order to guarantee that food items made by home enterprises are safe for people to eat, food safety oversight is essential. Research techniques used in this project include documentation studies, in-depth interviews, and observations, all part of a descriptive qualitative approach. Policies, resources, procedures, and supervisory outcomes are examined using the CIPP (Context, Input, Process, and Product) assessment paradigm. Inquiry into the North Bengkulu Regency Health Office's Food Safety Supervision Program as It Relates to the Distribution Permitting of Pirt (Household Industry Products). This study use a qualitative descriptive methodology to conduct an evaluation. The purpose of this study is to use the CIPP (Context, Input, Process, and Product) model to define, analyze, and evaluate the North Bengkulu District Health Office's food safety monitoring program for PIRT distribution licenses. Even though it was founded on relevant rules, the study is still facing a number of challenges, including a lack of operating funds, human resources, and food safety training materials for business players. Unfortunately, not all business actors have been able to participate in the Food Safety Extension Training (PKP) program because of restrictions on quotas and distribution medium. To provide thorough and sustainable supervision, it is necessary to enhance education, digitize information, and foster cross-sector synergy, even if more business actors are acquiring PIRT licenses. The goal of this research is to encourage more businesses to take responsibility for managing PIRT permits so that consumers may buy items made by these companies with peace of mind. Referring to national rules like the BPOM Regulation and the Minister of Health Regulation, the policy environment for food safety monitoring has a solid legal and regulatory foundation. At this time, there is insufficient infrastructure, human resources, financial backing, and officer technical knowledge to reach all PIRT business actors to their full potential. Following established protocols, the monitoring process has progressed through notification, document validation, field inspections, technical assistance, and final permit issuance recommendations. Businesses are now more conscious of the need of food safety requirements, and the number of PIRT permits has grown, according to monitoring. Keywords : Supervision, Food Safety, Distribution Permit, PIRT, Health Service, CIPP Evaluation.ABSTRAK Izin edar Produk Industri Rumah Tangga (PIRT) dikeluarkan oleh Dinas Kesehatan Kabupaten Bengkulu Utara, yang melaksanakan pemantauan keamanan pangan. Untuk menjamin keamanan pangan yang dihasilkan oleh usaha rumah tangga, pengawasan keamanan pangan sangat penting. Teknik penelitian yang digunakan dalam proyek ini meliputi studi dokumentasi, wawancara mendalam, dan observasi, yang semuanya merupakan bagian dari pendekatan kualitatif deskriptif. Kebijakan, sumber daya, prosedur, dan hasil pengawasan dikaji menggunakan paradigma penilaian CIPP (Konteks, Input, Proses, dan Produk). Penyelidikan Program Pengawasan Keamanan Pangan Dinas Kesehatan Kabupaten Bengkulu Utara Terkait Perizinan Edar PIRt (Produk Industri Rumah Tangga). Penelitian ini menggunakan metodologi deskriptif kualitatif untuk melakukan evaluasi. Tujuan penelitian ini adalah menggunakan model CIPP (Konteks, Input, Proses, dan Produk) untuk mendefinisikan, menganalisis, dan mengevaluasi program pemantauan keamanan pangan Dinas Kesehatan Kabupaten Bengkulu Utara untuk izin edar PIRT. Meskipun didasarkan pada aturan yang relevan, studi ini masih menghadapi sejumlah tantangan, termasuk kurangnya dana operasional, sumber daya manusia, dan materi pelatihan keamanan pangan bagi pelaku usaha. Sayangnya, belum semua pelaku usaha dapat mengikuti program Pelatihan Penyuluhan Keamanan Pangan (PKP) karena keterbatasan kuota dan media distribusi. Untuk memberikan pengawasan yang menyeluruh dan berkelanjutan, diperlukan peningkatan edukasi, digitalisasi informasi, dan sinergi lintas sektor, meskipun semakin banyak pelaku usaha yang telah memperoleh izin PIRT. Tujuan penelitian ini adalah untuk mendorong lebih banyak pelaku usaha agar bertanggung jawab dalam mengelola izin PIRT sehingga konsumen dapat membeli produk-produk yang diproduksi oleh perusahaan-perusahaan tersebut dengan tenang. Merujuk pada peraturan nasional seperti Peraturan BPOM dan Peraturan Menteri Kesehatan, lingkungan kebijakan untuk pemantauan keamanan pangan memiliki landasan hukum dan peraturan yang kuat. Saat ini, infrastruktur, sumber daya manusia, dukungan finansial, dan pengetahuan teknis petugas belum memadai untuk menjangkau seluruh pelaku usaha PIRT secara maksimal. Sesuai protokol yang telah ditetapkan, proses pemantauan telah berjalan melalui notifikasi, validasi dokumen, inspeksi lapangan, pendampingan teknis, dan rekomendasi penerbitan izin akhir. Pelaku usaha kini semakin sadar akan pentingnya persyaratan keamanan pangan, dan jumlah izin PIRT telah meningkat, menurut hasil pemantauan. Kata Kunci: Pengawasan, Keamanan Pangan, Izin Edar, PIRT, Dinas Kesehatan, Evaluasi CIPP.